Copper Sulfide Catalyzed Porous Fluorine-Doped Tin Oxide Counter Electrode for Quantum Dot-Sensitized Solar Cells with High Fill Factor - Satoshi Koyasu; Daiki Atarashi; Etsuo Sakai; Masahiro Miyauchi (International Journal of Photoenergy)
The performance of quantum dot-sensitized solar cell (QDSSC) is mainly limited by chemical reactions at the interface of the counter electrode. Generally, the fill factor (FF) of QDSSCs is very low because of large charge transfer resistance at the interface between the counter electrode and electrolyte solution containing redox couples. In the present research, we demonstrate the improvement of the resistance by optimization of surface area and amount of catalyst of the counter electrode. A facile chemical synthesis was used to fabricate a composite counter electrode consisting of fluorine-doped tin oxide (FTO) powder and CuS nanoparticles. The introduction of a sputtered gold layer at the interface of the porous-FTO layer and underlying glass substrate also markedly reduced the resistance of the counter electrode. As a result, we could reduce the charge transfer resistance and the series resistance, which were 2.5 [Ω] and 6.0 [Ω], respectively. This solar cell device, which was fabricated with the presently designed porous-FTO counter electrode as the cathode and a PbS-modified electrode as the photoanode, exhibited a FF of 58%, which is the highest among PbS-based QDSSCs reported to date.